The essential iron-sulphur protein Rli1 is a key determinant of oxidative stress resistance in Saccharomyces cerevisiae - Alhebshi, Alawiah (2014)
Reactive oxygen species (ROS) are linked to a range of degenerative conditions in humans, and may cause damage to an array of cellular components. However, it is unclear which cellular target(s) of ROS may primarily account for toxicity during oxidative stress. The sensitivity of iron-sulphur (Fe-S) clusters to ROS makes these candidate determinants of ROS mediated cell killing. Ribonuclease L inhibitor (Rli1p) is a highly conserved protein that is essential in all tested eukaryotes and archaea, but requires Fe-S clusters for its crucial functions in protein synthesis. Herein, the novel hypothesis that ROS toxicity is caused by loss of Rli1p function was tested. Rli1p activity (in nuclear export of ribosomal subunits) was impaired during mild oxidative stress in yeast. In addition, resistance to pro-oxidants was decreased by RLI1 repression and increased by RLI1 overexpression. This Rli1p-dependency was abolished during anaerobicity and accentuated in cells expressing the Fe-S cluster defective Rli1p construct, rli1C58A. The effects appeared specific to Rli1p as overexpression of other essential Fe-S proteins did not increase stress resistance. Methionine sulphoxide reductases (MSRs) and the Mn-superoxide dismutase (Sod2p) are known to help preserve the integrity of Fe-S clusters in cells. Here, these proteins’ antioxidant actions were shown to be at least partly mediated through Rli1p. Resistance to both chronic and acute oxidative stress was Rli1p-dependent. Further experiments indicated that Rli1p-dependent protein synthesis could be a critical target of ROS and, specifically, that Rli1p function may help to protect against ROS-induced mRNA mistranslation. The study indicated that Rli1p function is a primary biological target of ROS action, owing to its essential nature but dependency on ROS-labile Fe-S clusters. Such insights could offer new approaches for combating oxidative stress-related disease.